Clinical utilization of blinatumomab and inotuzumab immunotherapy in children with relapsed or refractory B‐acute lymphoblastic leukemia. Issue 1 (24th October 2020) - Contreras, Cristina F.; Higham, Christine S.; Behnert, Astrid; Kim, Kailyn; Stieglitz, Elliot; Tasian, Sarah K.
Abstract: Background: The treatment paradigm for patients with relapsed/refractory B‐cell acute lymphoblastic leukemia (rrALL) has been revolutionized given recent clinical trials demonstrating remarkable success of immunotherapies and leading to drug approvals by United States and European agencies. We report experience with commercial blinatumomab and inotuzumab use at two North American pediatric oncology centers in children and adolescents/young adults with B‐ALL. Procedure: Patients 0‐25 years old treated with the CD19 × CD3 bispecific T cell‐engaging antibody blinatumomab and/or the CD22 antibody‐drug conjugate inotuzumab from January 1, 2010, to June 1, 2018, were eligible. Disease status included relapsed B‐ALL in second or greater relapse, primary chemotherapy‐refractory B‐ALL, or B‐ALL complicated by severe infection precluding delivery of conventional chemotherapy. Results: We identified 27 patients who received blinatumomab and/or inotuzumab outside of clinical trials during the study period. Four of the 13 patients (31%) with relapsed disease achieved minimal residual disease (MRD)‐negative remission, and five patients (39%) underwent hematopoietic stem cell transplant (HSCT). In the 12 patients with primary chemorefractory B‐ALL treated with immunotherapy, 11 (92%) achieved MRD‐negative remission as assessed by flow cytometry; 10 patients (83%) underwent subsequent HSCT. Two patients with B‐ALL in MRD‐negative remission received blinatumomab due to severe infection and remained in remission after chemotherapy continuation. Conclusions: Blinatumomab and inotuzumab can induce deep remissions in patients with rrALL and facilitate subsequent HSCT or other cellular therapies. Blinatumomab can also serve as an effective bridging therapy during severe infection. The optimal timing, choice of immunotherapeutic agent(s), and duration of responses require further investigation via larger‐scale clinical trials.